The risk of knee pain and knee osteoarthritis in professional footballers - Parekh, Sanjay M. (2017)
Introduction: Knee osteoarthritis (KOA) is a common complex disorder. Although previously believed to be degenerative, KOA is in fact a regenerative condition, compensating against insults sustained at the joint. However, a failure of this compensatory repair process, especially in the presence of constitutional and local joint factors, increases the risk of KOA and inevitably leads to joint-failure (Dieppe and Lohmander, 2005, Arden and Nevitt, 2006, Sandell, 2012). Diagnosis of KOA may be made via clinical presentation, imaging, or using clinical algorithms, which may be a combination both in addition to biochemical diagnostic tests (Brandt et al., 2003). Knee pain (KP) is the most common symptom, and in the general population its prevalence is 25% (Peat et al., 2001a). Patients may also experience early morning stiffness of the joint and reduced function. Physician-observed signs include crepitus, restricted movement, and bony and soft tissue swellings (Abhishek and Doherty, 2013). Although considered the gold standard to diagnose KOA, plain film radiography is not without its limitations (Wick et al., 2012). Clinicians, however, favour radiography because it can easily discern two key features of the condition: joint space narrowing (JSN), a surrogate of cartilage loss, and the formation of osteophytes on the joint margin (Roemer et al., 2014). Assessment of radiographs is most commonly undertaken using Kellgren-Lawrence (KL) grade verbal descriptors (Altman et al., 1986a). The prevalence of radiographic KOA (RKOA) may be higher than KP, but there is a discordance between people reporting symptoms and those with structural change (RKOA) (Peat et al., 2001a, Bedson and Croft, 2008). A plethora of constitutional risk factors and joint-specific biomechanical factors increase the risk of KOA, including joint injury and occupation (Suri et al., 2012, Silverwood et al., 2015). One such occupation, which has a greater risk of injury are professional footballers (Drawer and Fuller, 2002) and knee injuries account for 17% of all footballing injuries (Ekstrand et al., 2011). Football is one of the most common team sports worldwide, with over 265 million people worldwide play the game (FIFA, 2007a), and of these, 110,000 are male professional footballers (FIFA, 2007b). Although perceived that that footballers are at great risk of long-term consequences such as KOA, due to their high risk of injury, the current evidence supporting this is limited (Kuijt et al., 2012, Tran et al., 2016). The previous studies observing KOA in footballers are difficult to generalise to the wider football population. This is for a number of reasons, including recruitment of inadequate sample, absence of inappropriate control groups, and differing case definitions, all resulting in a large variation in prevalence of KOA. Thus, there exists a need for a comprehensive study to determine the true prevalence and risk of KOA in retired professional footballers compared to the general population.